Comparison of load-velocity relationships in two bench press variations: weight stack machine vs Smith machine - Rodiles-Guerrero, L.; Pareja-Blanco, F.; Leon-Prados, J. A. (Sports Biomechanics, 2022)
Performing the bench-press (BP) exercise in a weight stack machine (WSM) is a common practice. However, no previous studies have analysed the load-velocity relationship in this BP variant. The purpose of this study was 1) to investigate the load-velocity relationship during BP exercise using a WSM; and 2) to compare the load-velocity relationship in this exercise in two conditions: WSM vs. Smith machine (SM). Twenty-six young men performed a BP progressive loading test to determine their one-repetition maximum and load-velocity relationship using a WSM. Additionally, 19 participants performed two progressive loading tests (WSM and SM). A high relationship was found between the relative load (%1RM) and mean propulsive velocity (MPV) (R2 = 0.97; SEE = 0.07 m/s) in the WSM. Moreover, significant differences were observed (p <.05) in the MPV values attained in every %1RM in WSM and SM from 30 to 75% 1RM. The close relationship between the MPV values and the %1RM in BP exercise using a WSM enables coaches to use the MPV to accurately monitor their athletes on a daily basis. The differences observed between WSM and SM in the %1RM and their respective MPVs indicate that different equations must be used for each exercise mode.